Pengaruh Fraud Diamond Terhadap Kecurangan Laporan Keuangan Perusahaan Sektor Industri Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia Tahun 2016-2020 - Banin Ufiana; Dedik Nur Triyanto (UNIVED Press, 2022)
This study aims to obtain empirical evidence regarding the effect of fraud theory on financial statements as measured using the F-Score method. The novelty of this research is the use of eight variables in this study to find out more specifically from the financial statements. This study uses the fraud diamond theory and agency theory. The population of this study consists of industrial goods and consumption companies listed on the Indonesia Stock Exchange. The population of this study consists of companies located in Indonesia. The research period is 2016 to 2020. The data used in this study is secondary data obtained from the company's annual financial statements. Purposive sampling technique was used to determine the research sample. There are 35 companies that are sampled. Factor analysis and logistic regression analysis methods were used as research methods. Based on the results of the study that ROA, RECEIV, BDOUT, AUDCHAGE, have a positive effect on the financial reporting of industrial and consumer goods companies listed on the Indonesia Stock Exchange. Furthermore, ACHANGE, LEV, AUDIT OPINION, DCHANGE have no effect on the financial statements of industrial and consumer goods companies listed on the Indonesia Stock Exchange.